A 'chicken or egg' discourse: Do we need skills for knowledge, or knowledge for skills? - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2006)
This short paper suggests a paradigm shift in technical education that provides a new teaching-learning cycle for acquiring knowledge and skills required by engineering students in order to enhance the success of the industrialization process.